Polypharmacy in the elderly - Negar Golchin; Scott H Frank; April Vince; Lisa Isham; Sharon B Meropol (Wolters Kluwer Medknow Publications, 2015)
Objective: The objective was to assess the frequency of polypharmacy and potential complications among local seniors. Methods: A cross-sectional convenience sample of 59 adults aged above 65 years was interviewed at Cuyahoga county (U.S. state of Ohio) senior programs. Polypharmacy was defined as more than five prescribed medications. Primary outcomes were frequent missed doses, one or more duplicate drug/s, and equal or more than one contraindicated drug combinations. Findings: Among seniors with the mean age of 76.9 years (25.4% male), 40.6% used multiple pharmacies and 35.6% had polypharmacy. Of all seniors with polypharmacy, about 57% had contraindicated drug combinations. Polypharmacy was associated with duplication (P = 0.02), but not frequent missed doses (P = 0.20). Conclusion: As shown by this study, polypharmacy was associated with duplicated therapy and contraindicated drug combinations. Improved communications among seniors, physicians, and pharmacists is necessary to minimize adverse consequences of polypharmacy.